Marketing Communication of Religious Tourism in Banjarmasin by the Regional Tourism Ambassador (Study on Nanang Galuh Banjar) - putri ayu hidayatur rafiqoh (Palakka : Media and Islamic Communication, 2020)
Banjarmasin as the capital of South Kalimantan has a variety of tourism, as the majority of Muslim, Banjarmasin also has several religious tourism objects that are visited by tourists, including the Mosque and the Tomb of Sultan Suriansyah, Masjid Raya Sabilal Muhtadin, Kembang Island , Jami Haur Kuning Mosque, and the Tomb of Habib Basirih. In this research, the writer wants to explore marketing communication conducted by Banjarmasin regional tourism ambassador or called Nanang Galuh Banjar in attracting tourists to visit religious tourism in Banjarmasin based on eight basic elements of marketing communication consisting of communicators, communicants, messages , media, obstacles, goals, feedback, and products. Which of these elements if used and applied properly can support success in the promotion process. In this case all parties must be aware of tourism, all can play a role as communicators, communicants, and people are able to collaborate with related sectors in the development of religious tourism with the aim of improving the economy of local communities, namely by providing business opportunities for typical crafts which can be a souvenir for visiting tourists. Then Nanang Galuh Banjar needs to make regular visitor data in order to know the effectively of marketing communication.